Peningkatan Literasi Keuangan Gen Z Untuk Membangun Generasi Cerdas Finansial - Vilantika, Elok; Santoso, Rahmat Agus (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
In order to prevent financial difficulties, financial literacy has now become essential for everyone, and the growing range of financial goods demands that people possess sufficient financial literacy. The Gen Z generation will eventually have to manage a growing number of complicated financial difficulties. Gen Z may steer clear of overwhelming debt, handle their finances sensibly, and get ready for a more secure financial future by becoming well-informed about money matters. This service's objectives are to give Gen Z high school students financial literacy skills, assess students' literacy levels, and enhance students' comprehension of literacy through the provision of materials from the service group. This program employs a workshop approach that is broken up into multiple phases of continuing activities. The goal of the program, which was to increase the financial literacy of PGRI Purwoharjo High School students, was accomplished with success. Students can participate in ongoing community service projects that teach them personal financial management skills and financial literacy on a regular basis.